The Effect of Welfare and Discipline on Member Performance in the Medan Satria Sector of the Bekasi City Metro Police, Metro Jaya Regional Police - Ferdy Mangihuttua Hutagalung; Harries Madiistriyatno; Widya Nengsih (Dinasti Publisher, 2026)
The performance of police officers is a crucial factor in supporting the effectiveness of service, protection, and law enforcement, especially in the Medan Satria Sector Police, Bekasi City Metro Police, Jakarta Metro Police, which has high operational task dynamics. Optimal performance is greatly influenced by the welfare conditions and level of work discipline of members. This study aims to analyze the influence of welfare and work discipline on member performance, both partially and simultaneously. This study uses a quantitative approach with a survey method. Data were collected through the distribution of 5-1 Likert scale questionnaires to 79 members of the Medan Satria Sector Police, Bekasi City Metro Police as research respondents. The data analysis technique used is multiple linear regression analysis with the help of the SPSS version 29 program. The results of the study indicate that welfare partially has a positive and significant effect on member performance with a t-value of 3.846 and a significance level of <0.001. Work discipline also has a positive and significant effect on member performance with a t-value of 4.664 and a significance level of <0.001. Simultaneously, welfare and work discipline have a significant effect on member performance, as indicated by the F-count value of 18.723 with a significance of <0.001. The coefficient of determination (R Square) of 0.330 indicates that welfare and work discipline are able to explain 33.0% of the variation in member performance, while the remaining 67.0% is influenced by other factors outside the research model. This finding confirms that increasing member welfare accompanied by the implementation of work discipline consistently and continuously is a strategic factor in improving the performance of police members in the Medan Satria Sector Police, Bekasi City Metro Police.